2020
DOI: 10.1186/s43045-020-00043-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D serum level in major depressive disorder and schizophrenia

Abstract: Background: Vitamin D is involved in many brain processes including neurological immune process, regulation of neurological factors, and neuroplasticity. Some studies have linked low serum vitamin D to major depressive disorder (MDD) and schizophrenia, while others have not shown any relationship. The study aimed to assess vitamin D level in patients with depression and those with schizophrenia. Sixty participants were recruited from outpatient clinics of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Studies have shown multiplex interactions between biological, psychological, and environmental factors giving rise to the association between obesity and depression [4]. Amongst the contributing factors of depression, vitamin D deficiency has increasingly drawn attention in recent years [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown multiplex interactions between biological, psychological, and environmental factors giving rise to the association between obesity and depression [4]. Amongst the contributing factors of depression, vitamin D deficiency has increasingly drawn attention in recent years [5].…”
Section: Introductionmentioning
confidence: 99%
“…This hormone binds to receptors in numerous brain regions including the hippocampus and cingulate cortex, which are involved in the pathogenesis of depression and other mental illnesses [6]. Many clinical studies have found depression, anxiety and cognitive impairment to be associated with low serum levels of 25-hydroxyvitamin D [25(OH)D], which is the major circulating form of vitamin D, in average weight people [5][6][7]. Recent research has also provided evidence for antidepressant properties of vitamin D supplementation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown multiplex interactions between biologic, psychologic, and environmental factors giving rise to the association between obesity and depression (4). Amongst the contributing factors of depression, vitamin D de ciency has increasingly drawn attention in recent years (5).…”
Section: Introductionmentioning
confidence: 99%
“…This hormone binds to receptors in numerous regions of the brain including the hippocampus and cingulate cortex, which are involved in the pathogenesis of depression and other mental illnesses(6). Many clinical studies have found depression, anxiety and cognitive impairment to be associated with low serum levels of 25-hydroxyvitamin D [25(OH)D], which is the major circulating form of vitamin D, in average weight people (5)(6)(7). Recent research has also provided evidence for antidepressant properties of vitamin D supplementation(8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…According to World Health Organization (WHO), MDD is a mood disorder with hormonal, neurochemical, and inflammatory alterations [1][2][3][4][5][6]. It has been reported that MDD is present twice in females than in males [7].…”
Section: Introductionmentioning
confidence: 99%